Compound Heterozygous Variants of the CPAMD8 Gene Co-Segregating in Two Chinese Pedigrees With Pigment Dispersion Syndrome/Pigmentary Glaucoma - Tan, Junkai; Zeng, Liuzhi; Wang, Yun; Liu, Guo; Huang, Longxiang; Chen, Defu; Wang, Xizhen; Fan, Ning; He, Yu; Liu, Xuyang (Frontiers in Genetics, 2022)
The molecular mechanisms underlying the pathogenesis of pigment dispersion syndrome and pigmentary glaucoma remain unclear. In pedigree-based studies, familial aggregation and recurrences in relatives suggest a strong genetic basis for pigmentary glaucoma. In this study, we aimed to identify the genetic background of two Chinese pedigrees with pigmentary glaucoma. All members of these two pedigrees who enrolled in the study underwent a comprehensive ophthalmologic examination, and genomic DNA was extracted from peripheral venous blood samples. Whole-exome sequencing and candidate gene verifications were performed to identify the disease-causing variants; in addition, screening the CPAMD8 gene were performed on 38 sporadic pigmentary glaucoma cases. Changes in the structure and function of abnormal proteins caused by gene variants were analyzed with a bioinformatics assessment. Pigmentary glaucoma was identified in a total of five patients from the two pedigrees, as were compound heterozygous variants of the CPAMD8 gene. No signs of pigmentary glaucoma were found in carriers of monoallelic CPAMD8 variant/variants. All four variants were inherited in an autosomal recessive mode. In additional 38 sporadic PG cases, 13 variants in the CPAMD8 gene were identified in 11 cases. This study reported a possible association between CPAMD8 variants and pigment dispersion syndrome/pigmentary glaucoma.